Current Approaches and Molecular Mechanisms for Directly Reprogramming Fibroblasts Into Neurons and Dopamine Neurons - Han, Fabin; Liu, Yanming; Huang, Jin; Zhang, Xiaoping; Wei, Chuanfei (Frontiers in Aging Neuroscience, 2021)
Parkinson's disease (PD) is mainly caused by specific degeneration of dopaminergic neurons (DA neurons) in substantia nigra of the middle brain. Over the past two decades transplantation of neural stem cells (NSCs) from fetal brain-derived neural stem cells (fNSCs), human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs) has been shown to significantly improve the symptoms of motor dysfunctions in PD animal models or PD patients. However, fNSCs and hESCs have ethnic concern and immune rejections whereas the iPSCs may have potential tumorigenicity caused by integration of the transgenes. Recent studies convinced that somatic fibroblasts can be directly reprogrammed to NSCs, neurons or specific dopamine neurons through overexpression of transcription factors, RNA-mediated reprogramming, chemical induction or in vivo transdifferentiation. The directly induced neurons (iN) or DA neurons (iDA) from somatic fibroblast cells has several advantages over the iPSC cells. Since these neurons produced through direct transdifferentiation do not pass through a pluripotent state, direct reprogramming is able to generate patient-specific cells and can overcome the safety problems of immune rejection and teratoma formation related to hESCs and iPSCs. However, there are some critical issues such as the low efficiency of direct reprogramming, biological functions and risks of the direct converted neurons, which hinder their clinical applications. Here we summarize the recent progress in methods, mechanisms, and future challenges of directly reprogramming somatic fibroblasts into neurons or dopamine neurons to speed up the clinical translation of these directly converted neural cells for treatment of PD and other neurodegenerative diseases. Direct reprogramming of somatic fibroblast cells into neurons or dopaminergic neurons represents an attractive cell source for treating the neurodegenerative diseases and as it uses the patient’s own cells to generate the required neurons to repair the degenerated neurons. The directly trans-differentiated neurons will have great clinical applications to repair the neurodegenerated diseases and brain injuries.